The main features of treatment in patients with iron deficiency anemia, which isa consequence of juvenile uterine bleedingwith chronic opisthorchiasis - I. D. Yevtushenko; M. M. Sidorova; L. S. Sotnikova; A. M. Dygai (Бюллетень сибирской медицины, 2008)
This article is presented whith the results of comparing assessment of clinical efficiency and medicine portability. This medicine is a stimulator of hematopoiesis (poetam-medicine which contains affinno refined antibodies to human recombinant erythropoietin). Besides there were rep resented the results of treatment with iron-containing medicine (Sulfate of iron 325 mg) which helps in case of anemia which is a consequence of juvenile uterine bleeding in puberty.